0347 Analysis of mortality in a pooled cohort of canadian and german uranium processing workers with no mining experience. (21st August 2017) - Zablotska, Lydia; Fenske, Nora; Schnelzer, Maria; Zhivin, Sergey; Laurier, Dominique; Kreuzer, Michaela
Abstract : Purpose: Long-term health risks of occupational exposures to uranium processing were examined to better understand potential differences with uranium underground miners and nuclear reactor workers. Methods: Two cohort studies of workers from Port Hope, Canada (1950–1999) and Wismut, Germany (1946–2008) employed in uranium milling, refining, and processing were pooled. Poisson regression was used to evaluate the association between cumulative exposures to radon decay products (RDP) and gamma-rays and causes of death potentially related to uranium processing. Results: The pooled cohort included 7431 workers (2 70 201 person-years of follow-up). Mean RDP exposures were lower than in miners while gamma-ray doses were higher than in reactor workers. Both exposures were highly correlated (weighted r=0.89). Risks of lung cancer and cardiovascular diseases (CVD) in males were increased but not significant and compatible with risks estimated for miners and reactor workers, respectively. Higher RDP-associated CVD risks were observed for exposures 5–14 years prior to diagnosis compared to later exposures and among those employed <5 years. Risks of solid cancers excluding lung cancer were increased, but not significant, both for males and females, while all other causes of death were not associated with exposures. Conclusions: In the largest study of uranium processing workers to systematically examine radiation risks of multiple outcomes from RDP exposures and gamma-rays, estimated radiation risks were compatible with risks reported for uranium miners and nuclear reactor workers. Continued follow-up and pooling with other cohorts of uranium processing workers are necessary for future comparisons with other workers of the nuclear fuel cycle.